Assessing Key Factors Influencing Rental Housing Choices and Affordability for Economically Weaker Sections (EWS): A Neighborhood Study in Delhi - Ekta; Vardhan, Prasanth (Alanya Üniversitesi, 2025)
The Economically Weaker Section (EWS) is constrained to live in slums and unauthorized colonies due to the lack of suitable housing options and affordability issues. Various factors such as building characteristics, financial constraints, and social considerations influence individuals' decisions regarding accommodation. A neighborhood in Delhi was chosen for a study to assess the importance of these factors for the EWS in rental housing. A total of 383 sample surveys were carried out to examine the socioeconomic variables and key factors influencing their choice of location, supplemented by 10 in-depth interviews to uncover hidden factors not typically found in existing literature. Principal Component Analysis was employed to identify the most crucial factors influencing accommodation choices. The study findings indicate that while the physical, locational, and economic aspects of rental housing are crucial, social factors also play a significant role. This research will offer invaluable insights to urban planners and policymakers to facilitate the provision of rental housing based on individual preferences in formulating housing policies.